2010
DOI: 10.1086/657401
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Survival of HIV‐Infected Children Receiving Antiretroviral Therapy in Thailand: A 5‐Year Observational Cohort Study

Abstract: Children who initiated ART as infants after meeting immunological and/or clinical criteria had a high risk of mortality which persisted beyond the first year of therapy. Among older children, those with severe wasting or low CD4 cell percentage at treatment initiation were at high risk of mortality during the first 6 months of therapy. These findings support the scale-up of early HIV diagnosis and immediate treatment in infants, before advanced disease progression in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
40
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 29 publications
13
40
1
1
Order By: Relevance
“…Over 75% of the children had viral log copies > 5.0 at baseline and after 12 weeks of HAART 66% of the children had an undetectable viral load (<400 copies per mL). These findings are consistent with the other studies findings which have shown that HAART with generic adult FDC are safe and effective for HIV-infected children in resource limited settings, despite initiation of treatment during advanced stages of the disease 7,11,12,21 . Among the children who failed therapy in the study, caregiver, and age were not significant risk factors for virologic failure in this study group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Over 75% of the children had viral log copies > 5.0 at baseline and after 12 weeks of HAART 66% of the children had an undetectable viral load (<400 copies per mL). These findings are consistent with the other studies findings which have shown that HAART with generic adult FDC are safe and effective for HIV-infected children in resource limited settings, despite initiation of treatment during advanced stages of the disease 7,11,12,21 . Among the children who failed therapy in the study, caregiver, and age were not significant risk factors for virologic failure in this study group.…”
Section: Discussionsupporting
confidence: 93%
“…In addition there appears to be poor immunologic reconstitution among the children who initiated ART with CD4 cell count <5%. These findings are similar to those reported in another Ugandan cohort of children which reported poor CD4 recovery compared to those in United Kingdom/Ireland probably due to lower CD4 cell count at ART initiation 28 A recent study from Thailand also reported that children with low CD4 percent and wasting at baseline were at high risk of mortality during the first 6 months of therapy 21 . These findings support the 2010 WHO recommendation of initiation of ART for children between 24-59 months at CD4<25% and those 5 years and older at CD4 absolute count<350 cells/ mm 3 , which was based on longitudinal data 29,30 .…”
Section: Discussionsupporting
confidence: 84%
“…2124 Our results extend these finding by assessing the one year outcomes in infants participating in a PMTCT-linked EID program. While the 20% mortality rate we observed in the first year of life among infants diagnosed with HIV at a median age of 7 weeks (IQR 6–8) is an improvement compared to the pre-ART era, it is much higher than the mortality observed in infants randomized to immediate ART in the CHER study (4% over a median follow-up of the full cohort of 40 weeks) conducted in South Africa.…”
Section: Discussionsupporting
confidence: 71%
“…It was estimated that earlier access to ART could have prevented 25% of HIV related death [8,9]. However, access to ART for children was only 12% among children under 15 years of age [1].…”
Section: Introductionmentioning
confidence: 99%